The Role of Mutation Testing in Patients with Chronic Myeloid Leukemia in Chronic Phase after Imatinib Failure and Their Outcomes after Treatment Modification: Single‑institutional Experience Over 13 Years - Chaitanya, Puligundla Krishna; Kumar, Karnam Ashok; Stalin, Bala; Sadashivudu, Gundeti; Srinivas, Maddali Lakshmi (Indian Journal of Medical and Paediatric Oncology, 2017)
Introduction: BCR-ABL1 kinase domain mutations represent the most frequent mechanism of resistance to tyrosine kinase inhibitor (TKI) therapy, being detected in 40%–50% of imatinib-resistant patients with chronic myeloid leukemia in chronic phase (CML-CP). Over 100 BCR-ABL1 single-point mutations have been reported in patients with imatinib-resistant CML. There were few studies reported from India on BCR-ABL kinase mutations in imatinib failure patients. We present our data on imatinib resistance mutation analysis (IRMA) and use of imatinib dose hike and 2nd-generation TKI at our institute. Materials and Methods: All patients with a diagnosis of CML in a university hospital from June 2003 to July 2016 and who were tested for IRMA in view of imatinib failure, those in CP, and age <18 years were included in the study. Results: A total of 2110 cases of CML reviewed and 269 cases of CML with imatinib failure were analyzed. The male to female ratio was 1.7:1. The median age at presentation was 36 years (range: 18–66 years). Among these, 26% were primary failures and 74% were secondary failures. The treatment was modified either as imatinib dose hike or nilotinib/dasatinib. Molecular response at 12 months was achieved in 25.7% in imatinib dose hike, 46.6% in nilotinib, and 53.8% in dasatinib arms. The 4-year overall survival in mutation detected group was 37.5% and in nonmutated group was 87.7%. Conclusion: Imatinib-resistant mutations were more common in the cases with secondary failure though not statistically significant. T315I mutation was the common mutation found in the study. Imatinib dose hike to the failure cases resulted in optimal hematological response rates.
Keywords: 2nd-generation tyrosine kinase inhibitor; chronic myeloid leukemia; imatinib resistance mutation analysis